The impact of COVID-19 on Sustainable Development Goals (SDG)1: Reducing poverty - Antunes, Nicole Moreira Cavacas dos (2023)
Poverty is a complex and multifactorial concept, and its evolution has long been debated. Progress has been made over the years to better assess and characterize poverty, optimizing indicators such as those associated with the Capacity method, the Sustainable Development Goals (SDGs) and the World Bank's proposal for the Multidimensional Poverty Index. The characterization of the pattern of poverty currently goes beyond monetary indicators and involves considering the multidimensionality of poverty, focusing on areas such as health, education and standard of living. In crisis contexts, this multidimensional approach must be particularly deepened, given the impact that a crisis situation can have at different levels on people's living conditions. This work analyses the role of the COVID-19 pandemic in the first of the SDGs, the eradication of poverty, and its main objectives are to measure poverty in Portugal as a multidimensional phenomenon and to identify the inequality profiles of poverty in Portugal in a recent context. In order to characterize poverty in all its dimensions, the guidelines of the World Bank indicators were used, as part of the construction of the Multidimensional Poverty Index. In methodological terms, a quantitative approach was chosen, based on the analysis of indicators from official secondary sources, produced, in the Portuguese case, by the National Statistics Institute (INE), as part of the operation of the National Statistical System. From the analysis carried out, it became clear that the COVID-19 pandemic has jeopardized the progress made in recent decades against poverty, as well as exacerbated disparities between groups of different characteristics. We argue that, although the overall figures seem to indicate an improvement in poverty to pre-pandemic values, certain groups are not represented by an average indicator and are more vulnerable to poverty. In Portugal, we conclude that women, the elderly and the population living in predominantly rural areas have been the most affected by the COVID-19 pandemic.